PENGARUH PERSEPSI MANFAAT, KEMUDAHAN, KERUMITAN, DAN SIKAP PENGGUNAAN TERHADAP MINAT UNTUK MENGGUNAKAN ERP - Fristiana Ningtyas; M Rafki Nazar (JAF (Journal of Accounting and Finance), 2019)
This research describes the individual acceptance by Accounting students of Telkom University on ERP using a variable Technology Acceptance Model (TAM) to perceived usefulness, ease of use, attitude use, and intention to use and also external variable of TAM to perceived complexity. This research aims to knowing the influence of perceived usefulness, ease of use, complexity, and attitude use on intention to use ERP of simultaneously and partial. A methods of this research used the quantitative approach to intends of descriptive. The kind of data is the primary data of respondent’s answers on the questionnaires from 207 students who were sample to Accounting students of Telkom University class of 2013 and 2014. Analysis of data in this research using descriptive analysis and multiple regression analysis. The results of data processing showed that variable perceived usefulness, ease of use, attitude use, and intention to use are on good category, while perceived complexity be in the not good. F test results showed that there were influence simultaneously between variables perceived usefulness, ease of use, complexity, and attitude use against the intention to use ERP. The results of the t test showed that the perceived usefulness variable it has significant of intention to use, perceived ease of use it has significant of intention to use, perceived complexity have significant of intention to use, and attitude use it has insignificant of intention to use.